Prolactin Expression in the Baboon (Papio hamadryas) Eye - María Lourdes Garza-Rodríguez; Iram Pablo Rodríguez-Sanchez; Rafael González-Álvarez; Maricela Luna; Carlos Horacio Burciaga-Flores; Fernando Alcorta-Nuñez; Orlando Solis-Coronado; Víctor Manuel Bautista de Lucio; Genaro A. Ramírez-Correa; Oscar Vidal-Gutiérrez; Diana Cristina Pérez-Ibave (Animals, 2022)
Prolactin (PRL) is a hormone expressed in lactotrophs cells of the pituitary gland in primates. Extra pituitary expression of PRL has been reported, including the eye; however, expression in the developing eye of primates is limited. The aim of the study was determining the expression of PRL and PRL receptor (PRLR) (mRNAs and proteins) in adult and fetal baboon (Papio hamadryas) ocular tissues. Methods: We analyzed PRL and PRLR in baboon eyes tissues by immunofluorescence. The mRNAs of PRL and PRLR were detected by RT-PCR, cDNA was cloned, and sequenced. Furthermore, we performed a phylogenetic analysis to identify the evolutionary forces that underlie the divergence of PRL and PRLR primate genes. Results: We observed the expression of PRL and PRLR (mRNAs and proteins) in all retinal cell lineages of fetal and adult baboon. PRL and PRLR fit the hypothesis of evolutionary purifying gene selection. Conclusions: mRNA and protein of PRL and PRLR are expressed in fetal and adult baboon retinal tissue. PRL may trigger autocrine and paracrine-specific actions in retinal cell lines.